Complementary Hydrogen Bonding Modulates Electronic Properties and Controls Self‐Assembly of Donor/Acceptor Semiconductors. Issue 48 (14th October 2016) - Black, H. T.; Yee, N.; Zems, Y.; Perepichka, D. F.
Abstract: A comprehensive investigation of the complementary H‐bonding‐mediated self‐assembly between dipyrrolo[2, 3‐ b :3′, 2′‐e]pyridine (P2P) electron donors and naphthalenediimide/perylenediimide (NDI/PDI) acceptors is reported. The synthesis of parent P2P and several aryl‐substituted derivatives is described, along with their optical, redox, and single‐crystal packing characteristics. The dual functionality of heteroatoms in the P2P/NDI(PDI) assembly, which act as proton donors/acceptors and also contribute to π‐conjugation, leads to H‐bonding‐induced perturbation of electronic levels. Concentration‐dependent NMR and UV/Vis spectroscopic studies revealed a cooperative effect of H‐bonding and π–π stacking interactions. This H‐bonding‐mediated co‐assembly of donor (D) and acceptor (A) components leads to a new charge‐transfer (CT) absorption that can be controlled throughout the visible range. The electronic interactions between D and A were further investigated by time‐dependent DFT, which provided insights into the nature of the CT transition. Electropolymerization of difuryl‐P2P afforded the first conjugated polymer incorporating H‐bonding recognition units in its main chain. Abstract : H‐bonded co‐assemblies : A supramolecular approach based on complementary H‐bonding was utilized for the organization of electron donor/electron acceptor pairs by taking advantage of the predictable interaction between dipyrrolopyridine donors and imide‐functionalized acceptors. The H‐bonding interaction not only provides a handle for solid‐state structural control, but also leads to electronic perturbation due to H‐bonding‐mediated charge redistribution in the π‐conjugated systems (see figure).